ESTUDO EPIDEMIOLÓGICO DAS AEROMONAS SPP., ATRAVÉS DE REP E ERIC-PCR, EM ABATEDOURO BOVINO - Martineli, T.m. [UNESP]; Rossi, O.d. [UNESP]; Cereser, N.d. [UNESP]; Kamimura, B.a [UNESP]; Cardozo, M.v. [UNESP]; Melo, P.c. [UNESP]; Nespolo, N.m. [UNESP] (Instituto Biológico, 2020)
The genus Aeromonas comprises important human pathogens and the gastroenteritises are the most common infections attributed to these microorganisms. Considering their importance as foodborne pathogens, the occurrence of Aeromonas spp. was studied on bovine carcasses and in the environment of an abattoir in State of São Paulo, Brazil, with the aim of defining the possible origin of these bacteria in the abattoir environment using molecular methods. Fifteen samples from 19 points were collected, totaling 285 units. The collecting points were: dry and wet skin, muscle surface of the carcasses during trimming process and refrigerated carcasses, operatives’ hands from the slaughter room before and during the work and from refrigerated rooms, knives, wall and floor from refrigerated room, water (chlorinated, nonchlorinated and from carcass washing), meat, intestinal content and slaughter room environment. Characterization of the genus was performed and the isolates were analyzed with REP (Repetitive Extragenic Palindromic) and ERIC-PCR (Enterobacterial Repetitive Intergenic Consensus PCR) techniques. A similarity of ? 99% was found only between one isolate from the muscle surface of one refrigerated carcass with one isolate from a hand. The molecular techniques did not enable the precise identification of the bacteria’s origin within the industry, but they permitted the inference that the operatives can spread Aeromonas in the slaughter environment.

O gênero Aeromonas compreende espécies consideradas importantes patógenos para os seres humanos, sendo que a principal ação patogênica delas corresponde às gastroenterites. Tendo em vista sua importância como patógeno de origem alimentar, a ocorrência de Aeromonas spp. foi estudada em carcaças bovinas e ambiente do abatedouro em uma indústria do Estado de São Paulo, com o intuito de definir a possível origem comum dessas bactérias no ambiente do frigorífico através de métodos moleculares. Foram colhidas 15 amostras de 19 pontos, totalizando 285 unidades. As amostras foram colhidas dos seguintes pontos: pele seca e úmida, superfície muscular das carcaças durante a toalete e das carcaças resfriadas, mãos dos funcionários antes e durante o trabalho na sala de abate e câmara de resfriamento, facas, parede e piso da câmara de resfriamento, água (clorada, não clorada e residuária da lavagem das carcaças), carne, conteúdo intestinal e ambiente da sala de abate. Foi realizada a caracterização do gênero e os isolados foram analisados pelas técnicas de REP (Repetitive Extragenic Palindromic) e ERIC (Enterobacterial Repetitive Intergenic Consensus)-PCR. Foi encontrada similaridade ? 99% somente entre um isolado de superfície muscular de uma carcaça resfriada com um isolado de mão. As técnicas moleculares não possibilitaram a identificação precisa da origem das bactérias na indústria, mas possibilitaram inferir que os manipuladores podem atuar como disseminadores delas no ambiente de abate.
EPIDEMIOLOGICAL STUDY OFAEROMONAS SPP. USING REP AND ERIC-PCR IN BOVINE ABATTOIR
Keywords: Aeromonas spp; molecular epidemiology; bovine slaughter; Aeromonas spp; epidemiologia molecular; abate bovino